And now you're back - Mansell, Jill (Headline Review, 2021)
"One magical winter's night in Venice, Didi fell in love. But it ended - and he left without even saying goodbye. Now, thirteen years on, Shay Mason is back. Of course the old spark is still there, but that's as far as it goes. Didi won't let the past unsettle her present: as manager of one of the most stunning hotels in the Cotswolds, she's happy at last and soon to be married. Anyway, Shay isn't staying. He's made a promise to his wayward father, that's all. He's going to keep it. And then he'll be gone. But Shay's return stirs up long-forgotten emotions in idyllic Elliscombe, and the scandal that led him to leave raises its head once again."--Publisher.